2018
DOI: 10.2147/ijnrd.s186121
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury among nonagenarians in Jordan: a retrospective case–control study

Abstract: BackgroundImprovements in health care systems worldwide have had notable effects on the life expectancy of older individuals. As a result, nonagenarians are emerging as a separate age group with distinct health care needs. The aim of this study was to evaluate the incidence of acute kidney injury (AKI), the mortality rates, and length of in-hospital stay among nonagenarians.MethodsThis is a retrospective case–control chart review of patients of age 90 years and above who were admitted to hospital. Patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…8,9 The risk for AKI was shown to be higher among octogenarians and nonagenarians. 10,11 Gender is suggested to increase the risk for AKI regardless of other co-morbidities, where males are at higher risk to get AKI as per Loutradis et al group, 12 In the present study, the number of males with AKI males' number was slightly higher than females. In addition, patients with hypertension were more likely to have AKI than others.…”
Section: Discussionsupporting
confidence: 49%
“…8,9 The risk for AKI was shown to be higher among octogenarians and nonagenarians. 10,11 Gender is suggested to increase the risk for AKI regardless of other co-morbidities, where males are at higher risk to get AKI as per Loutradis et al group, 12 In the present study, the number of males with AKI males' number was slightly higher than females. In addition, patients with hypertension were more likely to have AKI than others.…”
Section: Discussionsupporting
confidence: 49%
“…This could be related to functional and anatomical changes in the kidney that can happen with aging. 16–18 Different classifications for AKI are used, and incidence can vary based on the system employed. 10 …”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies involving AKI in elderly patients, we found that age above 60 years will have a higher risk for AKI, morbidity, mortality, length of hospital stay, and need for RRT [ 39 , 40 ]. A recent AKI in ICU epidemiology overview by Santos et al which included data of 67,033 patients from more than 300 ICUs from different regions of the world showed that mortality can range from 5% to 80% (highest) in septic patients, and the need for RRT can range from 0.8% to 59.2% [ 3 ].…”
Section: Discussionmentioning
confidence: 99%